miR-317 regulates the proliferation and apoptosis of duck follicle granulosa cells by targeting VIPR1 - Li Li; Qingwu Xin; Linli Zhang; Zhongwei Miao; Zhiming Zhu; Xiaopan Liu; Qiannan Cai; Wenli Shi; Bangzhe Zhao; Changtao Liu; Zhengkui Zhou; Azheng Liang; et al. (Poultry Science)
VIPR1 can specifically bind VIP, a PRL release factor, which promotes the secretion of PRL from the pituitary gland, and participates in the regulation of bird nesting behavior. The purpose of this study was to investigate the effects of miR-317 overexpression or silencing on VIPR1 gene and protein expression in duck follicle granulosa cells. The ovaries of Muscovy ducks were collected during the nesting and laying periods, and histological differences were analyzed via HE staining. Duck primary follicle granulosa cells were isolated and identified by immunofluorescence staining, after which the cells were transfected with miR-317, mimic-NC, miR-317 mimic, inhibitor-NC or miR-317 inhibitor Alterations in cell proliferation were then analyzed by EdU staining, and cell apoptosis was assessed by Annexin-V-FITC flow cytometry and TUNEL staining. Fluorescence quantitative PCR was used to assess the expression level of VIPR1 after miR-317 overexpression or silencing. Total protein was extracted from the follicle granulosa cells, and protein levels were analyzed via Western blotting. The results revealed that the nucleus of the ovarian granule in Muscovy ducks was more concentrated and distinct from the surrounding cells during the brooding period than during the laying period. More than 90 % of the cells were identified as duck follicle granulosa cells by immunofluorescence staining of FSHR and LHR. miR-317 expression was significantly higher in the miR-317 mimic-transfected group than in the miRNA-NC-transfected group (P < 0.01); similarly, miR-317 expression was significantly lower in the inhibitor-transfected group than in the miRNA inhibitor-transfected group (P < 0.01), indicating that miR-317 overexpression and interference vectors were successfully constructed and transfected into duck follicular granulosa cells. EdU staining revealed that the number of EdU-positive cells was significantly greater in the miR-317 mimic-transfected group than in the mimic-NC-transfected group (P < 0.05); after miR-317 silencing or inhibition, cell proliferation decreased, and the number of EdU-positive cells significantly decreased (P < 0.01). TUNEL staining revealed that the proportion of red, TUNEL-positive cells in the miR-317 inhibitor interference group was significantly greater than that in the miR-NC, miR-317 mimic, or inhibitor-NC group (P < 0.05). These results suggest that miR-317 inhibition promoted the apoptosis of duck follicle granulosa cells. Flow cytometry revealed that the percentage of apoptotic cells was 14.23 % and 22.75 % in the inhibitor-NC and miR-317 inhibitor groups, respectively (P < 0.01). Fluorescence quantitative PCR revealed that, compared with that in the corresponding control groups, VIPR1 gene expression was significantly lower in the miR-317 mimic group (P < 0.05) but significantly higher in the miR-317 inhibitor group (P < 0.05). Western blot analysis revealed that VIPR1 levels were significantly lower in the miR-317 mimic group than in the mimic-NC group (P < 0.05) but significantly greater in the miR-317 inhibitor group (P < 0.05). In summary, miR-317 inhibition promoted the apoptosis of duck follicle granulosa cells, and miR-317 overexpression promoted the proliferation of duck follicle granulosa cells and negatively regulated expression of the target gene VIPR1 at the gene and protein levels. This study further reveals the molecular mechanism underlying follicular atresia and serves as a reference for reducing the broodiness of Muscovy ducks.